Spotted gum produced in Brazil for structural solid wood: a physical and mechanical characterization (Nexo Revista Científica, 2024)
Numerous woods still require a detailed evaluation to understand structural potential. Spotted gum solid wood is among such species in which knowledge of its properties for construction is also required. The present study examined 16 physical-mechanical properties of the spotted gum wood (Corymbia maculata) to promote its use in the production of more sustainable bio-based buildings. Using the Brazilian NBR7190 standard code, two stable levels of moisture content were evaluated to figure out the wood behavior, the first at the 30 % saturation point and the second at the standardized dry point at 12 %. 13 spotted gum trees with different ages were collected from different plantations in Brazil to obtain samples from their trunks. Thus, 1959 determinations were analyzed to evaluate results from t-test at 5 % level of significance. From our significant, statistical, and comparative analyses, it was confirmed that spotted gum is suitable for structural uses, being a potential wood in tropical and subtropical regions of Latin America.